ENGLISH- RELIGIOUS TOLERANCE - A TOOL FOR INTERFAITH HARMONY IN PAKISTAN - Hafiz Ghulam Abbas Abbas; Imtiaz Ahmad Ahmad; Muhammad Sajjad Sajjad (دی اسکالر)
Pakistan provides home to people from diverse cultural, ethnic and religious backgrounds. Such variation has become responsible for misunderstandings and conflicts among different groups be it sectarian violence among Muslims throughout country, the language riots, or the continuous violence against non-Muslims. Most of the violence among religious communities is caused by misconceptions about other faiths. Unfortunately, Pakistan has become the victim of such social evils. Pakistan has to take some serious long term steps to eradicate this issue. It is duty upon her citizens and the state to create the environment of harmony and tolerance. In today’s modern world where distances mean nothing to us, we can promote peace and harmony in the light of Quran and other divine books. We can also promote positive behaviors and curb ill behaviors such as anxiety, extremism, angriness and violence. This paper aims to achieve the objective of promoting interfaith harmony, peaceful co-existence and acceptance among people belonging to different faiths in Pakistan and alike countries. For conduct of research doctrinal method has been employed with analytical approach.